A performance evaluation of the internet of things-message queue telemetry transport protocol based water level warning system - Sonklin, Kachane; Sonklin, Chanipa (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The internet of things (IoT) and message queue telemetry transport (MQTT) play crucial roles in connecting sensor networks, data exchange among diverse devices, and enabling various smart systems. Several studies have been conducted on IoT-MQTT-based applications because of their ease of implementation and deployment. It also offers real-time and reliable communication between a publisher and a subscriber. However, there is a lack of comprehensive studies covering overall performance metrics. Therefore, this paper aims to develop a water level warning system prototype and evaluate its performance through simulation experiments, focusing on critical metrics, such as latency, throughput, packet loss rate (PLR), packet delivery ratio (PDR), and availability at various data transmission rates. The results demonstrate that the proposed system achieves significantly lower latency, compared to existing solutions and achieves up to 98% availability and reliability with minimal packet loss. The experimental findings also reveal that higher data transmission rates lead to higher throughput and latency performance with lower performance in terms of availability, PDR, and sensor accuracy.